Examining The Capability Of People's Credit Bank In Langkat District In Overcoming Financial Problems Of Village Communities - Meigia Nidya Sari; Mustafa, Mustafa; Annisa Fajariah Damanik (International Journal of Economic Research and Financial Accounting, 2024)
This research aims to examine the ability of Rural Banks in Langkat Regency to overcome the financial problems of village communities. One of the very important needs of modern society today is a healthy and reliable financial system. The financial system even has a very basic role for society. Rural Bank is one of the institutions that uses a financial system and can provide financial information in the form of financial reports which can provide information to internal and external parties regarding the company regarding the financial situation and conditions within the company. The subjects in this research were the leadership, accounting department and operations department at the People's Credit Bank in Langkat Regency. The type of research is quantitative research with the data used are financial reports. Data collection techniques are interviews and documentation. Data analysis is CAMEL analysis which is used to assess the level of bank financial health based on capital, quality of productive assets (KAP), management, profitability and liquidity. The research results show that the level of bank financial health in terms of the capital aspect (CAR) in 2016, 2017, 2018 is within healthy criteria. The ratio of classified productive assets to productive assets in 2016, 2017, 2018 shows that the bank is in healthy criteria, while PPAPYD (Provision for Losses of Productive Assets Established) in 2016 is included in unhealthy criteria, whereas in 2017, 2018 the bank is in healthy criteria . The evaluation of management aspects in general management and risk management in 2016, 2017, 2018 shows criteria that are unhealthy and quite healthy. The profitability aspect, namely ROA in 2016, 2017, 2018 shows that the bank is in the healthy category, while BOPO in 2016, 2017, 2018 is included in the healthy criteria. The liquidity aspect, namely the LDR in 2016, 2017, 2018 is included in the healthy criteria, while the cash ratio in 2016, 2017, 2018 is included in the healthy criteria. Growth in the level of bank financial health at PT. BPR Langkat 2016, 2017, 2018 shows that the bank's financial health level is included in the healthy criteria.